Relaxor behavior of the conductive process for the system Pb0,91La0,09(Zr0,65Ti0,35)O3 + xMnO - Vega García, Arles (2022)
In this work, a study of the ceramic Pb0,91La0,09(Zr0,65Ti0,35)O3 + xMnO with x = 0,0; 0,01; 0,02 and 0,03 was carried out, The dielectric response of PLZT was measured using the impedance spectroscopy method, in the frequency range from 100 Hz to 10 MHz and at temperatures from 15 to 700 K, In the behavior of permittivity with frequency, a strong dispersion is reported for x = 0,0, This relaxing behavior becomes imperceptible with the increase of the Mn2+ cation, In the temperature range between 660 and 700 K, the doped samples showed a relaxation process by conductivity, studied by the Cole-Cole relaxation function, determining, in addition, the thermal evolution of the relaxation time τ, suggesting conductive processes by ion movement. The macroscopic activation energy was determined indicating a conduction process by oxygen vacancies.